POLA PEMBINAAN KEPRIBADIAN DAN KEAGAMAAN REMAJA MASJID AL-FATAH DI KELURAHAN GIRIAN INDAH KECAMATAN GIRIAN KOTA BITUNG - Prasetio Rumondor; Puspasari M. Y. Gobel (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2019)
AbstractThe rapid development of technology and the influence of the environment is very instrumental in shaping adolescents. There are many cases involving teenagers, this is a problem in the process of Islamic education in adolescents. Therefore, BTM Al-Fatah decided to establish youth mosque in order to avoid them from this influence. This research aimed to know how the coaching pattern of personality and religious adolescent Al-Fatah mosque. The data analysis used was qualitative descriptive analysis. The results showed that the emphasis is on the pattern of mosque youth coaching through the alignment of mosque youth activities with BTM activities, hence they might synergize and strengthen each other. There are studies about Islam to form an Islamic character for mosque youth and to support mosque youth activities such as quality training in Basic Leadership Training and skills training in computer training funded by BTM, attitude personality development, and refresher are almost similar to skills training. Efforts to overcome the problem are to continue to foster and support mosque youth activities in financial terms, creating a conducive environment when there are disputes between the management of BTM and the Imam of the Mosque and keep activating vacuum activities so that mosque youth can work and innovate in positive activities.